The Mask and the Play as Conceptual Components of M. Frisch’s Prose - Navasardyan, Syuzanna (International Journal of Language and Literary Studies, 2025)
The article explores the existentialist problem of duality and the search for one’s own identity in the prose of the Swiss writer Max Frisch. According to M. Frisch, a man should “define himself” in such a way that he can accept his ego, should find his role and his place in society according to his subjective view, even if it goes against the generally accepted norms and principles. “Mask” and artistic “role-playing”, as the main concepts of the writer’s prose, are “tools” and conductors of the author’s ideas. The author emphasizes the possibility and even the necessity of freedom of choice, which is achieved through “changing roles” and “changing masks”. Diary entries, which are of exceptional importance in the writer’s work, in the analyzed novels depart from the genre specificity, characteristic of both personal and literary diaries, and become part of the general “game” of the narrative. It is the diary “memories” that gives the author the opportunity for a sharp and unexpected change of different angles and perspectives. Reality in M. Frisch’s novels is so skillfully intertwined with virtuality that it is difficult to find the line where the author’s sincere monologue with himself ends and the author’s play of imagination begins.